Shen’s L-process on Berwald connection - Faghfouri, M.; Jazer , N. (Ukrains’kyi Matematychnyi Zhurnal, 2020)
The Shen connection cannot be obtained by using Matsumoto’s processes from the other well-known connections. Hence Tayebi–Najafi introduced two new processes called Shen’s C and L-processes and showed that the Shen connection is obtained from the Chern connection by Shen’s C-process. In this paper, we study the Shen’s C- and L-process on Berwald connection and introduce two new torsion-free connections in Finsler geometry. Then, we obtain all of Riemannian and non-Riemannian curvatures of these connections. Using it, we find the explicit form of hv-curvatures of these connections and prove that hv-curvatures of these connections are vanishing if and only if the Finsler structures reduce to Berwaldian or Riemannian structures. As an application, we consider compact Finsler manifolds and obtain ODEs.